Effect of triclosan-coated sutures for abdominal wound closure on the incidence of abdominal wound dehiscence: a protocol for an individual participant data meta-analysis - Timmer, Allard S.; Wolfhagen, Niels; Pianka, Frank; Knebel, Phillip; Justinger, Christoph; Stravodimos, Christos; Ichida, Kosuke; Rikiyama, Toshiki; Baracs, József; Vereczkei, András; Gianotti, Luca; Ruiz-Tovar, Jaime; et al. (BMJ open, 2022)
Introduction Acute abdominal wound dehiscence (AWD) or burst abdomen is a severe complication after abdominal surgery with an incidence up to 3.8%. Surgical site infection (SSI) is the biggest risk factor for the development of AWD. It is strongly suggested that the use of triclosan-coated sutures (TCS) for wound closure reduces the risk of SSI. We hypothesise that the use of TCS for abdominal wound closure may reduce the risk of AWD. Current randomised controlled trials (RCTs) lack power to investigate this. Therefore, the purpose of this individual participant data meta-analysis is to evaluate the effect of TCS for abdominal wound closure on the incidence of AWD. - Methods and analysis We will conduct a systematic review of Medline, Embase and Cochrane Central Register of Controlled Trials for RCTs investigating the effect of TCS compared with non-coated sutures for abdominal wound closure in adult participants scheduled for open abdominal surgery. Two independent reviewers will assess eligible studies for inclusion and methodological quality. Authors of eligible studies will be invited to collaborate and share individual participant data. The primary outcome will be AWD within 30 days after surgery requiring reoperation. Secondary outcomes include SSI, all-cause reoperations, length of hospital stay and all-cause mortality within 30 days after surgery. Data will be analysed with a one-step approach, followed by a two-step approach. In the one-step approach, treatment effects will be estimated as a risk ratio with corresponding 95% CI in a generalised linear mixed model framework with a log link and binomial distribution assumption. The quality of evidence will be judged using the Grading of Recommendations Assessment Development and Evaluation approach. - Ethics and dissemination The medical ethics committee of the Amsterdam UMC, location AMC in the Netherlands waived the necessity for a formal approval of this study, as this research does not fall under the Medical Research involving Human Subjects Act. Collaborating investigators will deidentify data before sharing. The results will be submitted to a peer-reviewed journal. - PROSPERO registration number CRD42019121173.
Gesehen am 02.06.2022